Determination of net energy content of soybean oil fed to growing pigs using indirect calorimetry. (15th September 2017) - Li, Enkai; LV, Zhiqian; Liu, Hu; Liu, Ling; Li, Yakui; Li, Zhongchao; Wang, Fenglai; Li, Defa; Zhang, Shuai
Abstract: The objectives of this experiment were: (i) to determine the net energy (NE) of soybean oil (SBO) fed to growing pigs using indirect calorimetry (IC); and (ii) to evaluate the effects of inclusion rate of SBO on heat production, oxidative status and nutrient digestibility in growing pigs. Eighteen growing barrows were allotted to three diets based on completely randomized design with six replicate pigs (period) per diet. Diets included a corn‐soybean meal basal diet and two test diets containing 5% or 10% SBO at the expense of corn and soybean meal. During each period, pigs were individually housed in metabolism crates for 14 days, including 7 days to adapt to feed, metabolism crate and environmental conditions. On day 8, pigs were transferred to the open‐circuit respiration chambers for measurement of daily O2 consumption and CO2 and CH4 production. During this time, pigs were fed one of the three diets at 2.4 MJ metabolizable energy/kg body weight (BW) 0.6 /day. Total feces and urine were collected and daily total heat production (THP) was measured from days 9 to 13 and fasted on day 14 to evaluate their fasting heat production (FHP). The results show that trends of decreased apparent total tract digestibility of neutral detergent fiber (linear, P  =   0.09) and acid detergent fiber (linear, P  =   0.07) were observed as the content of dietary lipids increased. The average THP for the three diets were 1326, 1208 and 1193 kJ/kg BW 0.6 /day, respectively. The FHP of pigs averaged 843 kJ/kg BW 0.6 /day and was not affected by diet characteristics. A reduction of the respiratory quotients in the fed state as the inclusion level of SBO increased was observed. In conclusion, the NE values of SBO we determined by indirect calorimetry were 33.45 and 34.05 MJ/kg dry matter under two inclusion levels. THP could be largely reduced when SBO is added in the feed, but the THP of SBO included at 5% in a corn‐soybean meal diet is not different from the THP of SBO included at 10%.